2018
DOI: 10.3389/fpsyg.2018.01479
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of Uncertainty and Three-Valued Truth Tables

Abstract: Psychological research on people's understanding of natural language connectives has traditionally used truth table tasks, in which participants evaluate the truth or falsity of a compound sentence given the truth or falsity of its components in the framework of propositional logic. One perplexing result concerned the indicative conditional if A then C which was often evaluated as true when A and C are true, false when A is true and C is false but irrelevant“ (devoid of value) when A is false (whatever the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…22 (McGee, 1989; Kaufmann, 2009; Gilio and Sanfilippo, 2014; Sanfilippo et al, 2018). Baratgin, Politzer, Over and Takahashi (2018) have confirmed that the abstract (non-causal) biconditionals has a well corresponding truth table to pARIs. In the subjective probability theory developed by De Finetti, conditional probabilities are atomic and that they correspond to conditional events (de Finetti, 1964).…”
Section: Discussionsupporting
confidence: 63%
“…22 (McGee, 1989; Kaufmann, 2009; Gilio and Sanfilippo, 2014; Sanfilippo et al, 2018). Baratgin, Politzer, Over and Takahashi (2018) have confirmed that the abstract (non-causal) biconditionals has a well corresponding truth table to pARIs. In the subjective probability theory developed by De Finetti, conditional probabilities are atomic and that they correspond to conditional events (de Finetti, 1964).…”
Section: Discussionsupporting
confidence: 63%
“…Of the various philosophers who have considered a trivalent treatment of indicative conditionals along these lines, several—notably Adams, Mackie, and Ducrot—were particularly interested in expounding the connection between conditionals and supposition that is suggested by the Ramsey test. Indeed, recent psychological studies have supported the trivalent theory (e.g., Baratgin, Over, & Politzer, 2013; Baratgin, Politzer, Over, & Takahashi, 2018; Politzer, Jamet, & Baratgin, 2020; Politzer, Over, & Baratgin, 2010), and it has been taken up in psychological work as the main representative of a “suppositional” theory of conditionals, supplanting the “no truth‐value” theory popularized in philosophical work under the influence of Adams, Edgington, and Bennett. In addition, several more recent formal studies have expanded on de Finetti's observation that his theory enforces the equation between probabilities of conditionals and conditional probabilities, showing that it circumvents a variety of triviality results (Lassiter, 2020; Mura, 2009; Paneni & Scozzafava, 2003; Rothschild, 2014).…”
Section: The Trivalent Semantics For Indicative Conditionalsmentioning
confidence: 96%
“…Informally, one can see the jumps , † , and ‡ as corresponding to the operations of extending a given labeled tree to another labeled tree, where the sequents that are added result from applying the rules of CC/TTm 'upside down', that is, going from a sequent to all its possible premises according to the CC/TTm rules. 6 Now we construct a search tree for every sequent, that is, a labeled tree where the above jumps are systematically applied as many times as possible. For every sequent define (for a limit ordinal ):…”
Section: Proposition 34 For Every Triple Of Sets Of Formulae and Exactly One Of The Two Following Cases Is Givenmentioning
confidence: 99%